A Covering Property via Generalized Fuzzy Preopen Sets - A. Swaminathan; Margret Sheela (Utilitas Mathematica, 2025)
In 1965, Zedeh [4] established the foundation of fuzzy set theory. Shortly thereafter, in 1968, Chang[1] introduced the concept of fuzzy topology. Within the realm of classical Topology, Csa’sza’r[3] introduced the idea of generalized topology.